THE ROLE OF EMOTION-REGULATION STRATEGIES IN THE RELATIONSHIP BETWEEN DEMOGRAPHIC FACTORS AND DEPRESSION TENDENCIES - ÉVA KÁLLAY; SEBASTIAN PINTEA (Studia Universitatis Babes-Bolyai, 2018)
ABSTRACT. The drastic changes characteristic to our times force individuals to face rapidly changing life conditions, resulting in an increasing number of individuals who cannot adequately adapt. There is a plethora of research indicating differences in depression tendencies between gender differences and educational levels. However, the cognitive and emotional mechanisms that may explain such differences are understudied. Our study investigates which cognitive emotion‐regulation strategies mediate the relationship between gender/education, and depressive tendencies. Our results indicate a significant relationship between gender and depression tendencies; women having higher levels of depressive symptoms. We also found a significant relationship between education and depression; lower levels of depressive symptoms for participants with higher levels of education. Female participants use to a higher degree strategies as self‐blame, acceptance, rumination, putting into perspective, and catastrophizing. Concerning mediational models, the relationship between gender and depression tendencies is mediated by self‐blame, acceptance, rumination and catastrophizing, while the relationship between education and depression tendencies is mediated by acceptance, catastrophizing, and others blame. In conclusion, even if social factors are more intuitive and easier to identify in the form of social categories (gender/education groups), behind these categories stand different psychological profiles, generated by differences in using psychological mechanisms such as emotion‐regulation strategies. Our study points out the need to identify such subtle mechanisms that can explain the unequal distribution of distress in the population.